Digging up the Gender Spectrum: Patriarchy to Intersectionality - Adhikari, Ashok Kumar (PRAGYAN A Peer Reviewed Multidisciplinary Journal, 2021)
This paper aims to depict the overall situation of gender and its prevalent variants throughout the globe, in particular to Nepal. The dichotomy of sex and gender, on the other hand, is another debated issue giving rise to number of feminist movements. These movements have direct impacts entailing the gender practices in Nepali society and culture. As such, Nepal’s journey through the channel of gender spectrum leads a roadmap to a more liberal perspective of gender.